The Role of Business Schools in Ethics Education in Iceland: The Managers’ Perspective - Throstur Sigurjonsson; Vlad Vaiman; Audur Arnardottir
This article explores managers’ views on various ways in which business schools can contribute to providing solid ethics education to their students, who will ultimately become the next generation of business leaders. One thousand top level managers of Icelandic firms were approached and asked a number of questions aimed at establishing their view on the relationship between ethics education and the role of business schools in forming and developing business ethics education. Icelandic businesses were badly hurt by the 2008 crisis, and therefore Iceland provides an interesting foundation for an empirical study of this sort as the aftermath of the crisis has encouraged managers to consciously reflect on the way their business was and should be conducted. Based on the results of the survey, a few main themes have developed. First, it appears that according to practicing managers, business schools should not be held responsible for employees’ unethical behavior. Nevertheless, managers believe that business schools should assist future employees in understanding ethics by including business ethics in teaching curricula. Second, managers believe that the workplace is not where ethics are learned, while also insisting that former students should already have strong ethical standards when entering the workplace. Third, managers call for business schools not only to contribute more to influencing students’ ethical standards, but also to reshape the knowledge and capabilities of practicing managers through re-training and continuous education. Based on the results of the study, the article also offers some recommendations on how to begin reformulating the approach to business ethics education in Iceland, and perhaps elsewhere. Copyright Springer Science+Business Media Dordrecht 2014 Ethics, Higher education, Business schools, Iceland